Voluntariness and type of digital device usage: A study in terms of Vygotsky's cultural–historical perspective - Shatskaya, Arina; Gavrilova, Margarita; Chichinina, Elena (Frontiers in Psychology, 2023)
Introduction In recent years, exposure to digital devices during the development stages of a child has been steadily increasing. Exploring the relationship between children's digital device exposure and their voluntariness still shows quite contradictory results. Screen time is the most studied factor on this issue. The purpose of the present study was to suggest the type of digital device used is another factor in addition to screen time. In accordance with the research hypothesis, the use of digital devices as a psychological means is related to higher voluntariness scores. Methods The study sample was recruited from Moscow kindergartens and schools: preschoolers aged 5–6 years (n = 408) and 6–7 years (n = 351) and schoolchildren aged 7–8 years (n = 253) and 9–10 years (n = 101). The study participants took part in a voluntariness assessment performed via executive functions' (EF) evaluation as well as in a semi-structured interview to identify the type and frequency of digital device usage. Results There are three findings of the present study, which are given as follows. First, the “frequency of digital device usage” predictor proved its statistical significance for verbal working memory, inhibition, and cognitive flexibility at 7–8 years, and for verbal working memory at 6–7 years. Second, the number of children who use digital devices as a psychological means increases as they grow older. Third, the number of children who use digital devices as a psychological means tends to demonstrate higher mean scores for any executive function skills at 6–7 and 9–10 years and for visual and verbal working memory at 7–8 years. Multiple regression models did not confirm the significance of the “type of digital devices usage” predictor for executive function skills considering the participants' individual characteristics. Discussion “Type of digital devices usage” predictor is assumed to be more applicable to children at the end of primary school and older when exploring executive function skills in the context of children's digital device exposure.